The Influence of Social Media on the Marital Harmony of STDIIS Students: An Islamic Family Law Perspective - Izzuddin Hanif Al Atsary; Muhammad Yassir (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the influence of social media usage on the marital harmony of married students at the Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i (STDIIS) Jember from the perspective of Islamic Family Law (Fiqh al-Usrah). The research method employed is a qualitative case study design with an Islamic legal sociology approach. Primary data were gathered from 30 married student respondents through structured online questionnaires. The findings reveal that social media usage exerts an ambivalent impact; it serves as a vital supportive tool for 36.7% of couples in Long Distance Marriages (LDM), yet concurrently triggers domestic friction such as phubbing (33.3%), digital jealousy (33.3%), and neglect of domestic responsibilities (30%). Normatively, phubbing is classified as a form of taqshir (negligence) regarding the partner's intrinsic rights, while digital jealousy is mitigated through the principle of Sadd al-Dhari’ah via device password disclosure (60%). Despite these frictions, respondents demonstrate a high level of digital maturity by consistently choosing conflict resolution through tabayyun and private deliberation to protect Hifz al-Irdh (family honor) rather than engaging in destructive cyber-venting behavior.